DFT STUDY OF GEOMETRIC ISOMERIZATION AND KETO–ENOL TAUTOMERIZATION OF DIHYDROXYFUMARIC ACID - BOLOCAN, Natalia; DUCA, Gheorghe (Studia Universitatis Babeș-Bolyai Chemia, 2021)
A total of 45 isomers of dihydroxyfumaric acid (DHF), including 23 keto and 22 enediol forms, were identified and their geometrical isomerization and tautomerization was studied at the B3LYP level of theory using the 6–311++G(2df,2p) basis set in the gas phase and aqueous solution, and three most stable enediol structures were identified. Interconversions between the enediol forms and the keto forms proceed through two paths: (1) proton transfer ( ≈ 135–160 kJ mol-1) and (2) internal rotation ( ≈ 0.15–75 kJ mol-1). Keto–enol tautomeric reactions of dihydroxyfumaric acid were investigated for the three most stable enediol structures. It was found that the activation energy and the free activation energy is in the range of 230–310 kJ mol-1 for the gas phase and by 50-80 kJ mol-1 lower in water, and TSs structures reveal that the carboxylic oxygen that forms the hydrogen bond in the enediol structure is involved in the mechanism of proton transfer. Furthermore, equilibrium constants have been calculated, along with the forward and reverse reaction rates for the isomerization and tautomerization reactions of the three most stable enediol structures, in gas and water.